The effect of insulin resistance on amygdale glucose metabolism alterations in experimental Alzheimer’s disease - Ya. V. Gorina; Yu. K. Komleva; O. L. Lopatina; A. I. Chernykh; A. B. Salmina (Бюллетень сибирской медицины)
Purpose. Glucose metabolism is tightly regulated in the brain. Aberrant glucose metabolism is an important feature of neurodegenerative diseases, as inAlzheimer’s disease. The transport of glucose to the cell membrane is realized through the activity of insulin-regulated aminopeptidase (IRAP) which controls transfer of glucose transporter to the plasma membrane. IRAP is considered as one of the key markers of insulin resistance in Alzheimer’s disease. However, the question of the mechanism of the action of the IRAP remains open. The aim of the study was to study the effect of IRAP expression on cells of the neuronal and glial lineage, glucose transporter (GLUT4) expression in the brain amygdala on emotional memory in animals with experimental Alzheimer’s disease.Materials and methods. The study was performed with two experimental models of Alzheimer’s disease in mice. The experimental group was mice of the CD1 line, males aged 4 months (Alzheimer’s disease model with the intra-hippocampal administration of beta-amyloid 1-42 (1 µl) bilaterally in the CA1 area). The control group was mice of the CD1 line, males aged 4 months (sham-operated animals with the intrahippocampal administration of Phosphate buffered salin (1 µl) bilaterally in the CA1). The genetic model of Alzheimer’s disease is the B6SLJ-Tg line mice (APPSwFlLon, PSEN1*M146L*L286V) 6799Vas, males aged 4 months. The control group consisted of C57BL/6xSJL mice, males aged 4 months. Evaluation of emotional memory was carried out using “Fear conditioning” protocol. Expression of molecule-markers of insulin-resistance in the amygdala was studied by immunohistochemistry followed by confocal microscopy.Results. Aberrant associative learning and emotional memory was revealed in animals with an experimental model of Alzheimer’s disease. A decrease (p ≤ 0,05) of IRAP expression on cells of neuronal and glial nature, associated with GLUT4 down-regulation was detected in amygdala of brain in animals with experimental Alzheimer’s disease.Conclusion. Decreased number of IRAP-immunopositive neuronal and astroglial cells, as well as IRAP+/ GLUT4+ in cells of amygdala in animals with an experimental model of Alzheimer’s disease, indicates the development of insulin resistance in amygdala of brain, which was in correlation with the hippocampus in performing cognitive functions and memorizing associated with emotionally colored events.